SPECIFICATION A MODEL FOR STUDY OF PERIURBAN SERVICES - Morales, Francisco Espinoza; Lirios, Cruz García; Sanchez, Arturo Sánchez; Campas, Celia Yaneth Quiroz; Ruíz, Gilberto Bermúdez; González, María del Rosario Molina (International Journal of Engineering Technologies and Management Research, 2020)
Social representations are visions of the everyday world that is historically constructed alongside the dissemination of media intensifies their audiences. In this sense, the printed media availability and water policy has not only been systematically reduced to opinions by the press, but also two logics have been grown on the credibility of the information and the verifiability of it. In this sense, this study exposes the lines of discussion for the analysis of tandem policies and agenda setting in the availability and supply of water. The results show frames from newspaper audiences are considered promoters of a relative deprivation that is the conformism of the service quality of public water supplies.